Blockchain-Based Zakat Management for Transparency and Poverty Alleviation in Somalia - Musa, Mohammad (International Journal of Sharia Studies, 2025)
Ideally, zakat functions as a powerful instrument of social justice and poverty alleviation within Muslim communities, including in Somalia—a country with significant zakat potential and urgent socioeconomic needs. In reality, however, weak governance structures, limited transparency, fragile institutions, and low public trust continue to hinder effective zakat management. This situation reflects a gap between the normative aspiration of zakat as a pillar of communal welfare and the suboptimal implementation observed on the ground. This study aims to explore a blockchain-based zakat management model as an innovative approach to enhance transparency, accountability, and distribution efficiency in Somalia. Using a library-based method and a qualitative-descriptive approach, this research examines academic literature, international institutional reports, and publications related to blockchain technology and zakat governance. The findings demonstrate that blockchain enables transparent transaction recording, smart-contract mechanisms for targeted disbursement, and increased public trust in zakat institutions. Thus, blockchain technology holds strategic potential to establish trustworthy, inclusive, and impactful zakat governance, contributing meaningfully to poverty alleviation efforts in Somalia.